Muscle power during intravenous sedation - Nobuyuki Matsuura (Elsevier, 2017)
Intravenous sedation is effective to reduce fear and anxiety in dental treatment. It also has been used for behavior modification technique in dental patients with special needs. Midazolam and propofol are commonly used for intravenous sedation. Although there have been many researches on the effects of midazolam and propofol on vital function and the recovery profile, little is known about muscle power. This review discusses the effects of intravenous sedation using midazolam and propofol on both grip strength and bite force. During light propofol sedation, grip strength increases slightly and bite force increases in a dose-dependent manner. Grip strength decreases while bite force increases during light midazolam sedation, and also during light sedation using a combination of midazolam and propofol. Flumazenil did not antagonise the increase in bite force by midazolam. These results may suggest following possibilities; (1) Activation of peripheral benzodiazepine receptors located within the temporomandibular joint region and masticatory muscles may be the cause of increasing bite force. (2) Propofol limited the long-latency exteroceptive suppression (ES2) period during jaw-opening reflex. Thus, control of masticatory muscle contraction, which is thought to have a negative feedback effect on excessive bite force, may be depressed by propofol.